(untitled) - Urdang, Laurence (New York, 1997)
The book provides thorough coverage of current English from around the world, including a rich array of regional and idiom antic expressions, slang, colloquialisms, and so forth. All words and phrases that are recognized as being typical of a particular variety of English, whether geographical or stylistic, are carefully labeled to enhance accurate word choice. It combines the best of both styles through a unique double-access system: headwords are organized alphabetically and there is an extensive synonym index, which list more than 250,000 additional words and phrases
Keywords: Ametricanisms,English language; Dictionaries,Synomyms and antonyms; United States